Cell Surface Rescue of Kidney Anion Exchanger 1 Mutants by Disruption of Chaperone Interactions - Patterson, Sian T. (American Society for Biochemistry and Molecular Biology, 2010)
Mutations in the human kidney anion exchanger 1 (kAE1) membrane glycoprotein cause impaired urine acidification resulting in distal renal tubular acidosis (dRTA). Dominant and recessive dRTA kAE1 mutants exhibit distinct trafficking defects with retention in the endoplasmic reticulum (ER), Golgi, or mislocalization to the apical membrane in polarized epithelial cells. We examined the interaction of kAE1 with the quality control system responsible for the folding of membrane glycoproteins and the retention and degradation of misfolded mutants. Using small molecule inhibitors to disrupt chaperone interactions, two functional, dominant kAE1 mutants (R589H and R901stop), retained in the ER and targeted to the proteasome for degradation by ubiquitination, were rescued to the basolateral membrane of Madin-Darby canine kidney cells. In contrast, the Golgi-localized, recessive G701D and the severely misfolded, ER-retained dominant Southeast Asian ovalocytosis (SAO) mutants were not rescued. These results show that functional dRTA mutants are retained in the ER due to their interaction with molecular chaperones, particularly calnexin, and that disruption of these interactions can promote their escape from the ER and cell surface rescue.